Solar disinfection of natural river water with low microbiological content (10–103 CFU/100 ml) and evaluation of the thermal contribution to water purification. (1st January 2017) - Vivar, M.; Pichel, N.; Fuentes, M.
Highlights: SODIS was effective with natural water containing wild bacteria (10 3  CFU/100 ml). But total inactivation was not achieved according to WHO standards (0 CFU/100 ml). Clostridium perfringens was highly resistant to SODIS, with only a 43% reduction. Water temperatures near the microbial optimum growth values might be antagonistic. Current electronic sensors require more research to be suitable for natural water. Abstract: Natural river water with low concentrations of wild bacteria strains (10–10 3  CFU/100 ml) was subjected to solar disinfection over the span of a year under different climatic conditions (temperate climate). After 6 h of sun exposure, SODIS was effective in all seasons for E. coli, Enterococcus spp. and total coliforms, although total disinfection was not achieved according to WHO standards (0 CFU/100 ml). Only for Enterococcus spp. complete inactivation was reached in the experiments corresponding to autumn and summer, with initial microbial populations of 10 2  CFU/100 ml. The most resistant microorganism was Clostridium perfringens that with initial concentrations of 10–10 3  CFU/100 ml, a 43% reduction was only achieved after the SODIS treatment in the best case. The contribution of the thermal component was also studied under real-time conditions to separate this effect from the total SODIS process. Results have shown and confirmed that temperatures near the optimum growth temperature of the different microorganisms can have an antagonistic effect on solar disinfection and slow down the process.